Genome Structures and Transcriptomes Signify Niche Adaptation for the Multiple-Ion-Tolerant Extremophyte Schrenkiella parvula. Issue 4 (21st February 2014) - Oh, Dong-Ha; Hong, Hyewon; Lee, Sang Yeol; Yun, Dae-Jin; Bohnert, Hans J.; Dassanayake, Maheshi
Abstract : Genome structural variations in Arabidopsis-related extremophile modify the transcriptome, endowing competence to survive multiple-ion salt stress in its natural habitat . Abstract: Schrenkiella parvula (formerly Thellungiella parvula ), a close relative of Arabidopsis ( Arabidopsis thaliana ) and Brassica crop species, thrives on the shores of Lake Tuz, Turkey, where soils accumulate high concentrations of multiple-ion salts. Despite the stark differences in adaptations to extreme salt stresses, the genomes of S. parvula and Arabidopsis show extensive synteny. S. parvula completes its life cycle in the presence of Na +, K +, Mg 2+, Li +, and borate at soil concentrations lethal to Arabidopsis. Genome structural variations, including tandem duplications and translocations of genes, interrupt the colinearity observed throughout the S. parvula and Arabidopsis genomes. Structural variations distinguish homologous gene pairs characterized by divergent promoter sequences and basal-level expression strengths. Comparative RNA sequencing reveals the enrichment of ion-transport functions among genes with higher expression in S. parvula, while pathogen defense-related genes show higher expression in Arabidopsis. Key stress-related ion transporter genes in S. parvula showed increased copy number, higher transcript dosage, and evidence for subfunctionalization. This extremophyte offers a framework to identify the requisite adjustments of genomic architecture and expression control for a set of genes found in most plants in a way to support distinct niche adaptation and lifestyles.